Impact of recycling sustainability on organizational performance - Odia, Uchechukwuka Linus (Linguistics and Culture Review, 2021)
This is empirical research focusing on the impact of recycling sustainability on Organizational performance in Nigeria. To achieve the objective of this study, a sample of 10 publishing houses in four major cities in Delta State was adopted, and these cities include Asaba, Warri, Sapele, and Oghara. Given that Nigeria is the regional publishing powerhouse in West Africa with newspaper publications selling in the whole region, likewise, textbook publishers in Nigeria dominate the regional market. The industry contributes about 10% of the GDP and is one of the fastest-growing in the manufacturing sector. Unfortunately, Nigeria does not produce most of the raw materials for publishing. All paper materials used in Nigeria are imported, and the costs are rising with the reliability of the sources dwindling. In addition, the publishing industry in Nigeria is faced with a high rate of waste and returns. The study focused on the impact of adopting recycling sustainability as a possible solution to the dwindling raw materials, increasing costs, and high rate of returns. It used a stratified random sampling approach and a descriptive research design.